Application of Cognitive Theory in Science Independent Learning for Grade 5 Students of SDN 1 Sukasada - Made Diah Prabaswari Putri; Ni Ketut Suarni; I Gede Margunayasa (Psikostudia : Jurnal Psikologi, 2025)
This research was conducted as a response to the problem of the lack of focus of grade 5 students at Sukasada 1 State Elementary School in learning science. This research aims to overcome this problem by applying cognitive theory in independent science learning. The research subjects consisted of 5th grade students who were divided into two groups, namely the experimental group and the control group, using a purposive random sampling technique. Data regarding science learning ability was collected using the test method, and data analysis was carried out using the Polled Variance T test to test the homogeneity of data variance. The results showed that the application of cognitive theory in independent science learning significantly increased students' understanding and focus on learning compared to the control group. These findings confirm the effectiveness of cognitive theory in increasing students' learning independence and contributing to the development of more optimal learning strategies, both in curriculum preparation and the application of learning methods that can improve the quality of science learning in elementary schools. Penelitian ini dilakukan sebagai respons terhadap permasalahan kurangnya fokus siswa kelas 5 Sekolah Dasar Negeri 1 Sukasada dalam pembelajaran IPA. Penelitian ini bertujuan untuk mengatasi permasalahan tersebut dengan menerapkan teori kognitif dalam pembelajaran mandiri IPA. Subjek penelitian terdiri dari siswa kelas 5 yang dibagi menjadi dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol, menggunakan teknik purposive random sampling. Data mengenai kemampuan pembelajaran IPA dikumpulkan melalui metode tes, dan analisis data dilakukan menggunakan uji T Polled Varians untuk menguji homogenitas varians data. Hasil penelitian menunjukkan bahwa penerapan teori kognitif dalam pembelajaran mandiri IPA secara signifikan meningkatkan pemahaman dan fokus belajar siswa dibandingkan dengan kelompok kontrol. Temuan ini menegaskan efektivitas teori kognitif dalam meningkatkan kemandirian belajar siswa serta memberikan kontribusi dalam pengembangan strategi pembelajaran yang lebih optimal, baik dalam penyusunan kurikulum maupun penerapan metode pembelajaran yang dapat meningkatkan kualitas pembelajaran IPA di Sekolah Dasar.